2013
DOI: 10.1038/srep02307
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-current properties of superconducting amorphous tungsten nanostrips

Abstract: The voltage-current (V-I) characteristics of tungsten (W) strips patterned by focused-ion-beam assisted deposition were studied at different temperatures and various magnetic fields applied perpendicular to the strips. At fields of 1 Tesla (T) and 2 T, a scaling behavior was observed in V-I isotherms, which can be fitted by quasi-three-dimensional (quasi-3D) vortex-glass (VG) to liquid transition theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 29 publications
13
49
0
Order By: Relevance
“…Sun et al . 45 estimated value larger than 8 T at 2 K. Through our resistance-temperature-magnetic field (RTH) experiments, we have also observed more than 8 T. Moreover, we carried out RTH experiments up-to 14 T, which has been performed for the first time on FIB-deposited W material and estimated . Note that the reported values are estimated using 90% resistance transition value and hence, cannot be compared with the value of parent pure W material.…”
Section: Discussionmentioning
confidence: 76%
“…Sun et al . 45 estimated value larger than 8 T at 2 K. Through our resistance-temperature-magnetic field (RTH) experiments, we have also observed more than 8 T. Moreover, we carried out RTH experiments up-to 14 T, which has been performed for the first time on FIB-deposited W material and estimated . Note that the reported values are estimated using 90% resistance transition value and hence, cannot be compared with the value of parent pure W material.…”
Section: Discussionmentioning
confidence: 76%
“…At T > T g , the sample is in the vortex-liquid state, the I–V curves exhibit ohmic behavior and the resistance remains constant even at small current I. Previous theoretical and experimental studies show that z = 4~7 and ν = 1~2 are reasonable values for the VG phase transition 27 . To obtain a good scaling performance, we have D = 2, ν = 1.9, and z = 4.2.…”
Section: Resultsmentioning
confidence: 87%
“…In VG theory, with the decrease in T, the mobile vortex (i.e., vortex-liquid state) will finally be pinned by the randomly distributed pinning centers, reaching the superconducting state (i.e., vortex-glass state). Therefore, the I–V curves at different temperatures near the liquid-glass phase transition temperature (T g ) can be scaled into two different branches by the scaling law 2729 :where v is the exponent of the vortex-glass correlation length ξ g and ξ g diverges at T g as:z is the dynamical critical exponent, D is the number of dimensions, and f ± are the scaling functions above and below T g . Above T g , being in the vortex-liquid phase, there is a finite linear resistance for a low current limit I → 0 27 :and the I–V curve becomes nonlinear for large I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was recently studied theoretically and showed a rich phase diagram [52]. These W–C films are also convenient for fundamental studies regarding the nature of the vortex-glass to vortex-liquid transition under one-dimensional pinning potential given that previous studies in flat W–C films without artificial pinning have shown good scaling behavior [18]. Additionally, the W–C material could be the building block of arrays of superconducting islands on a normal metal, as was recently investigated for dynamic critical behavior studies [53].…”
Section: Resultsmentioning
confidence: 99%